ENHANCING ENGLISH VOCABULARY ACQUISITION AMONG YOUNG LEARNERS THROUGH VISUAL AIDS - Umami, Risa (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
In the era of globalization, mastering English is crucial for international communication. As English becomes increasingly important, many elementary schools have incorporated it into their curriculum, focusing on vocabulary as the foundation for developing other language skills, such as listening, speaking, reading, and writing. This study explores the effectiveness of using pictures as a tool to enhance vocabulary acquisition among elementary students. A qualitative descriptive method was employed, with a sample of 30 students from a local elementary school. The study found that pictures played a significant role in increasing student engagement, comprehension, and vocabulary retention. Visual aids helped students connect new words to their meanings more easily, reducing misunderstandings and facilitating better learning outcomes. Specifically, pictures improved students' ability to recall vocabulary and made the learning process more enjoyable. These findings suggest that incorporating visual aids into vocabulary instruction can be a highly effective strategy for enhancing language learning in young learners.